Strategic Management Accounting : A Practical Guidebook with Case Studies - Li, Wing Sun (Singapore : Springer Singapore : Imprint: Springer, 2018)
This book serves as a guide to strategic management accounting. It introduces new and useful concepts on how to collect, analyse, and evaluate options to enable managers to steer corporate directions and write strategic plans for the long-term success of the corporation. Starting with basic techniques and the latest strategic management approaches, the book then presents cases that show the techniques employed step by step. By demonstrating how easily the ideas can be translated into action, it is a valuable resource for business practitioners, as well as for students taking advanced management accounting courses.
Part I. Management Accounting Basics -- Chapter 1. Cost Behavior and Marginal Concepts -- Chapter 2. Cost-Volume-Profit Relationships, and Theory of Constraints -- Chapter 3. Value Concepts -- Part II. Managing Customers -- Chapter 4. Customer Account Analysis -- Chapter 5. Strategic Customer Account Management -- Part III. Managing Competitors -- Chapter 6. Competitor's Accounting -- Chapter 7. Game Theory in Strategic Pricing -- Part IV. Managing Value -- Chapter 8. Strategic Value Analysis -- Chapter 9. Business Valuation -- Chapter 10. Strategic Merges and Acquisitions.
Description based on publisher-supplied MARC data.
Keywords: Accounting; Bookkeeping .; Business consultants; Leadership; Accounting/Auditing.; Business Consulting; Business Strategy/Leadership.; Financial Accounting